L'Europe «représentée» dans deux récits poétiques : Nous, l'Europe, banquet des peuples (2019) de Laurent Gaudé et Eurodance (2018) d'Aurélien Bellanger - Almeida, José Domingues de (2021)
This paper aims to provide an eminently representational reading of the state and destiny of Europe in two texts which claim to be lyric, even elegiac, and which provide a poetic and political reflection on the evolution of our continent at a very specific moment marked by the disintegration of the European institutional project, the rise of new facets of nationalism and identity insecurity. In these two texts, one of which has been brought to the stage, it is a simultaneously complex and lucid portrait of Europe that is painted.